2021
DOI: 10.1002/joa3.12461
|View full text |Cite
|
Sign up to set email alerts
|

2021 ISHNE/HRS/EHRA/APHRS collaborative statement on mHealth in Arrhythmia Management: Digital Medical Tools for Heart Rhythm Professionals

Abstract: This collaborative statement from the International Society for Holter and Noninvasive Electrocardiology/Heart Rhythm Society/European Heart Rhythm Association/Asia Pacific Heart Rhythm Society describes the current status of mobile health (“mHealth”) technologies in arrhythmia management. The range of digital medical tools and heart rhythm disorders that they may be applied to and clinical decisions that may be enabled are discussed. The facilitation of comorbidity and lifestyle management (increasingly recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 442 publications
0
13
0
7
Order By: Relevance
“…Great progress has been achieved in both clinical diagnosis and management of rhythm diseases [129][130][131][132][133], thanks also to the fundamental knowledge generated through the preclinical modeling of this assorted class of disturbs. Disease modeling has extremely helped to gain more understanding of the causes and the pathomechanistic insights underlying cardiovascular diseases.…”
Section: Heart Rhythm Diseases: Clinical Signs Underlying Causes and Modeling Approachesmentioning
confidence: 99%
“…Great progress has been achieved in both clinical diagnosis and management of rhythm diseases [129][130][131][132][133], thanks also to the fundamental knowledge generated through the preclinical modeling of this assorted class of disturbs. Disease modeling has extremely helped to gain more understanding of the causes and the pathomechanistic insights underlying cardiovascular diseases.…”
Section: Heart Rhythm Diseases: Clinical Signs Underlying Causes and Modeling Approachesmentioning
confidence: 99%
“…However, the disadvantages that come with these tools are false-positive episodes of AF due to substantial electrical or motion artifact, misclassified rhythms, and unavailability of other arrhythmias classification. 17 Currently, there are several types of digital health tools available for monitoring, which can be divided into ECG tracing technologies and non-ECG tracing technologies. Handheld devices, smartwatch ECG, and smartphone ECG devices are some examples of ECG tracing technologies while photoplethysmography, oscillometry, and mechanocardiography are some examples of non-ECG tracing technologies.…”
Section: Digital Health Tools For Atrial Fibrillation Monitoringmentioning
confidence: 99%
“…Therefore, verification from the treating physician is needed to prevent overtreatment. 17 The Apple Heart Study is a good example to show that the probability of irregular pulse notification was low in the general population. 19 From 2017 to 2018, the trial observed the identification of AF through a smartwatch application during typical use.…”
Section: Digital Health Tools For Atrial Fibrillation Monitoringmentioning
confidence: 99%
“…Las nuevas tecnologías han simplificado la monitorización, pero el rendimiento de la estrategia a utilizar debe adap-tarse a cada situación particular. En la tabla 1 se resume la definición de las principales estrategias utilizadas extractadas de los documentos de consenso de las principales sociedades científicas del mundo (9) .…”
Section: ¿Cuándo Hacer Tamizaje De Fibrilación Auricular?unclassified
“…Debemos tener conciencia que inevitablemente estamos en medio de una revolución digital en la práctica médica, que es crucial asumir la responsabilidad de su aplicación y desarrollo y que estos objetivos son compartidos por médicos, pacientes e industria (2) . Las principales sociedades científicas del mundo han publicado en los últimos años recomendaciones para el uso y el desarrollo de las tecnologías digitales en la asistencia médica, en general y en particular para patología cardiovascular (3)(4)(5)(6)(7)(8)(9) . ¿Cuál es la aceptación de la sociedad en cuanto al uso y preferencias de esta tecnología disponible en salud?…”
unclassified